2010 IEEE Frontiers in Education Conference (FIE) 2010
DOI: 10.1109/fie.2010.5673668
|View full text |Cite
|
Sign up to set email alerts
|

Student preferences between open-ended and structured game assignments in CS1

Abstract: Introductory computer programming courses (CS1) traditionally are plagued with high failure and drop-out rates. In an attempt to change these negative outcomes, games have often been introduced into computing curricula as learning activities and programming projects. This paper builds on prior work to determine (a) the type of game assignment that students prefer (i.e., structured game assignments [those for which the entire assignment is completely described] or open-ended game assignments [those for which on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Games are widely used to motivate students to learn programming [53,130,179,333,371,688], and have the advantage of lending themselves to more creative open-ended projects. Although students prefer to have structured assignments [132], they enjoy the opportunity to be creative when supported by an appropriate framework [35,301,395], and can even be enlisted to develop games for the learning of programming [588]. However, there is some evidence that the course context is not as important as good structure and good support in the course [295].…”
Section: Teaching Deliverymentioning
confidence: 99%
“…Games are widely used to motivate students to learn programming [53,130,179,333,371,688], and have the advantage of lending themselves to more creative open-ended projects. Although students prefer to have structured assignments [132], they enjoy the opportunity to be creative when supported by an appropriate framework [35,301,395], and can even be enlisted to develop games for the learning of programming [588]. However, there is some evidence that the course context is not as important as good structure and good support in the course [295].…”
Section: Teaching Deliverymentioning
confidence: 99%
“…Problem-based learning was mainly project-based, answering open-ended questions [12], [13]. Through the review, they found evidence that students preferred structured assignments [14].…”
Section: B Introductory Programmingmentioning
confidence: 99%
“…Literature of learning programming contains many research studies that have been proposed to face these problems with different approaches; for example: games [33,34], robots [35], pair programming [36,37].…”
Section: Cs1 Coursementioning
confidence: 99%